Remote Sensing-Based Assessment of Seagrass Health and Carbon Sequestration in Wakatobi National Park - Eka Fauziah; Nurjannah Nurdin; Yayu A. La Nafie; Muhammad Banda Selamat; Supriadi Supriadi; Muhammad Rijal Idrus; Xuelei Zhang (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2025)
The Wakatobi waters, part of the Wakatobi National Park, host an extensive seagrass ecosystem; however, detailed information on its exact coverage remains relatively scarce. To address this, remote sensing technology is essential for providing a comprehensive overview of the seagrass ecosystem's condition over a broad area in a relatively short time. This study focuses on analyzing the condition of seagrass through both direct measurements and remote sensing, as well as evaluating its carbon content, particularly in Wangi-Wangi Island. Conducted from January to December 2023, the research employed an exploratory approach with purposive sampling to categorize seagrass coverage as low, medium, and high. Seagrass types and total coverage were measured using 1m × 1m quadrat transects. Organic carbon content was analyzed using the Walkley and Black (WB) method, while satellite imagery from Landsat 8 (2013) and Landsat 9 (2023) was used to assess the overall coverage and distribution of seagrass. The study identified nine seagrass species, including Cymodocea serrulata, Cymodocea rotundata, Enhalus acoroides, Halodule pinifolia, Halodule uninervis, Halophila ovalis, Syringodium isoetifolium, Thalassodendron ciliatum, and Thalassia hemprichii. Seagrass conditions ranged from low (26.20%) to medium (62.50%) and high (80.48%). The seagrass area declined from 2,209.4 ha in 2013 to 2,044 ha in 2023. Average carbon content was 4.29 Mg C.ha-1, with carbon stock estimates between 755,844.82 and 11,984,600.79 Mg C.ha-1. The decline in seagrass coverage in Wangi-Wangi Island is attributed to environmental degradation and human activities, including coastal development. Denser seagrass areas were found to have greater carbon sequestration potential, emphasizing the ecological significance of maintaining healthy seagrass ecosystems.